2008
DOI: 10.1159/000129657
|View full text |Cite
|
Sign up to set email alerts
|

Rubidium, Salami and Depression

Abstract: Background: Depression may induce malnutrition, but, as a paradoxical hypothesis, malnutrition may induce depression. This relationship, of course, depends on how we define malnutrition. Current Knowledge: Rubidium is a trace element strongly linked with depression, and is deficient in uremia sufferers. However, in uremic patients, rubidium deficiency is more evident during predialysis, as it is at least partially corrected during dialysis and after transplantation. It seems that diet restrictions might be the… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2014
2014
2024
2024

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 12 publications
(1 citation statement)
references
References 55 publications
0
1
0
Order By: Relevance
“…Almeida et al (2020) and Stojsavlkević et al (2022) both reported decreased serum concentrations in HD patients compared to a healthy control group [15,34]. Rubidium appears to be lost in the dialysis fluid during the dialysis process [66,91] and patients with renal failure also appear to have a decreased intake of Rb [92]. Together, these factors may explain the decreased Rb concentrations in HD patients.…”
Section: Discussionmentioning
confidence: 99%
“…Almeida et al (2020) and Stojsavlkević et al (2022) both reported decreased serum concentrations in HD patients compared to a healthy control group [15,34]. Rubidium appears to be lost in the dialysis fluid during the dialysis process [66,91] and patients with renal failure also appear to have a decreased intake of Rb [92]. Together, these factors may explain the decreased Rb concentrations in HD patients.…”
Section: Discussionmentioning
confidence: 99%